Pengaruh Pandemi COVID-19 dan Variabel Sosial Ekonomi terhadap Prevalensi Ketidakcukupan Konsumsi Pangan di Indonesia Tahun 2021 - Laksmana Putri, Calivi Kezia; Zhafarina, Nadaa; Putri, Natasya Yunita; Kartiasih, Fitri (Politeknik Statistika STIS, 2023)
The COVID-19 pandemic at the end of 2019 caused several obstacles to achieve the SDGs. The Prevalence of Undernourishment (PoU), which is an indicator of the second SDGs goal, has increased from 2020 to 2022. This increase is allegedly due to the influence of the COVID-19 pandemic. This research was conducted to find out whether COVID-19 was included in the factors that influenced the increase in PoU or other factors that influenced it. The quantitative method used in this study, namely correlation analysis and multiple linear regression to obtain a model that shows how much influence the independent variables used have on the PoU. Based on this analysis, two variables were obtained that had a significant influence on the PoU, namely the percentage of poor people and the amount of rice production. So it can be concluded that even though COVID-19 had an effect on PoU, it was not significant. The factors that have a significant effect on PoU are the aspect of food affordability which is represented by the variable percentage of poor people and the aspect of food availability which is represented by the variable amount of rice production.